Comparison of the oral microbiome of patients with generalized aggressive periodontitis and periodontitis-free subjects. (March 2019) - Schulz, Susanne; Porsch, Martin; Grosse, Ivo; Hoffmann, Katrin; Schaller, Hans-Günter; Reichert, Stefan
Highlights: Detection of distinct differences in the composition of the oral microbiome according to the periodontal diagnosis. Porphyromonas gingivalis was proven to be the strongest indicator for aggressive periodontitis. A more complex view of the oral microbiome allows a more detailed elucidation of the etiology of severe periodontitis. The results pave the way for an individual adjustment of the periodontal therapy. Abstract: Objective: The primary objectives of the study were to assess differences in complex subgingival bacterial composition between periodontitis-free persons and patients with generalized aggressive periodontitis (gAgP). Background: The composition of the oral microbiota plays an important role for both oral and systemic diseases. However, the complex nature of the oral microbiome and its homeostasis is still poorly understood. Material and methods: We compared the microbiome of 13 periodontitis-free persons to 13 patients with gAgP. The 16S rRNA genes were amplified, targeting the V3/V4 region using the MiSeq platform. Results: In total, 1713 different bacterial species were mapped according to the Greengenes database. Using the Shannon index, no significant differences in alpha diversity were found between the two study groups. In principal component and linear discriminant analyses, disease-specific differences in beta diversity of the microbiome composition were evaluated. Bacteroidetes, Spirochaetes, and Synergistetes were more abundant in gAgP whereas Proteobacteria, Firmicutes, and Actinobacteria were associated with a healthy periodontium. At the bacterial species level, we showed that Porphyromonas gingivalis is the strongest indicator of gAgP. Treponema denticola and Tanerella forsythia of the "red complex" as well as Filifactor alocis were among the ten best biomarkers for gAgP. Conclusions: These results broaden our knowledge of disease-specific differences in the microbial community associated with generalized AgP. A more complex view of the composition of the oral microbiome describes the etiology of generalized AgP in more detail. These results could help to individually adapt periodontal therapy in these patients.